A viagem circular de Paul Le Cointe (1900-1901) - Sanjad, Nelson (Museu Paraense Emílio Goeldi, 2025)
This tribute encouraged new research on Le Cointe's life and work, including the inventory of his documentary and scientific legacy. Throughout the research carried out in recent years, several documentary collections related to Le Cointe were located in France, duly referred to in this edition. In Brazil, relevant collections were also collected to better understand Le Cointe's career. In addition to the digital version of the diary, the Goeldi Museum preserves Le Cointe's correspondence with Emílio Goeldi and Jacques Huber, photographs, archaeological artifacts, botanical samples and the French scientist's library. Le Cointe's work has become the best known and most widely read in both Brazil and France.